PENGARUH CITRA MEREK KOPI KENANGAN TERHADAP KEPUTUSAN PEMBELIAN PRODUK OLEH KONSUMEN(Survei pada followers Instagram Kopi Kenangan) - Rida Nur Pratiwi, (2020)
THE EFFECT OF KOPI KENAGAN'S BRAND IMAGE ON PURCHASING DECISIONS (Survey on followers of Kopi Kenangan's Instagram) Rida Nur Pratiwi Abstract Indonesia is the 3rd largest coffee producer in this world. A coffee tree that planted in Indonesia is widely used by other coffee shops from another country where beverage products have high prices. Starting from these conditions, Edward Tirnata was motivated by opening a brand for coffee shop because he thought to take up business opportunities. The purpose he opened Kopi Kenangan is to be a bridge between coffee lovers who are able to buy coffee products from the international coffee shops and coffee lovers who are only able to buy coffee from traditional markets. Kevin's coffee shop business was established in 2017 and now the number of outlets has reached 200 outlets. The business has been growing rapidly is certainly due to the role of consumers who make purchasing decisions for Kopi Kenangan's products. The theory used in this study was the hierarchy of effect models. The research used quantitative approach with the type of explanatory method with a sample of 100 respondents. Related to the correlation test, the result of study indicates a very strong influence brand image on purchasing decisions. Not only that but also the results of the regression test and the coefficient determination test indicate there is an influence of brand image on purchasing decisions by consumers. The results of hypothesis testing in this study indicate that Ho is rejected and Ha is accepted because the value of count is greater than t table. It means there is the effect between brand image and purchasing decision. Key words : Brand image, Purchase Decision, Coffee Industry Growth in Indonesia.